Southern Hemisphere Westerly Winds have modulated the formation of laminations in sediments in Lago Fagnano (Tierra del Fuego, Argentina) over the past 6.3 ka. (18th September 2022) - Vizcaino, Alexis; Jimenez‐Espejo, Francisco J.; Dunbar, Robert B.; Mucciarone, David; García‐Alix, Antonio; Neugebauer, Ina; Ariztegui, Daniel
Abstract : Tierra del Fuego in Argentina is a unique location to examine past Holocene wind variability since it intersects the core of the Southern Hemisphere Westerly Winds (SHWW). The SHWW are the most powerful prevailing winds on Earth. Their variation plays a role in regulating atmospheric CO2 levels and rainfall amounts and distribution, both today and in the past. We obtained a piston core (LF06‐PC8) from Bahía Grande, a protected sub‐basin at the southern margin of Lago Fagnano, the largest lake in Tierra del Fuego. This article focuses on the uppermost 185 cm of this core, corresponding to laminated sediment from the last ~6.3 ka. Laminations consist of millimetre‐scale paired dark and light layers. Previous studies and new geochemical analysis show that the dark and light layers are characterized by differing concentrations of Mn and Fe. We attribute the distribution of Mn and Fe to episodic hypolimnic oxic–anoxic variations. The age model suggests an approximately bidecadal timescale for the formation of each layer pair. We propose a new model of these redox changes with the SHWW variations. The most likely phenomenon to produce complete water‐column mixing is thermobaric instability, which occurs in colder winters with low‐intensity SHWW (El Niño‐like conditions). In contrast, windier winters are characterized by higher temperatures and reduced mixing in the water column, facilitating a decline in oxygen concentration. Laminations, and the inferred presence of periodic hypolimnion redox changes, are common features of the past ~6.3 ka. Geochemical proxy variability is compatible with an intensification of El Niño/Southern Oscillation activity during the past ~2 ka.